Three new species of Orthocladius subgenus Eudactylocladius (Diptera: Chironomidae) from Norway - Sæther, Ole. A. (Zootaxa, 2004)
The male imagines of Orthocladius (Eudactylocladius) priomixtus sp. n, O. (E.) schnelli sp. n. and O. (E.) musester sp. n. and the tentatively associated pupa of O. (E.) priomixtus are described. The male imago of O. (E.) priomixtus differs from the closely related O. (E.) subletteorum Cranston by having a preapical projection of the gonostylus and more numerous setae on the squama. The tentatively associated pupa has oval spine patches on tergite II and absent or reduced pedes spurii B as the tentatively associated O. (E.) subletteorum, but lacks any pleural spinules. O. (E.) schnelli has strong and dense microtrichiae on the gonostylus and a well sclerotised anal point. O. (E.) musester resembles O. (E.) fuscimanus (Kieffer), but has a more developed inferior volsella of the gonocoxite and a conspicuously broad cibarial pump. A revised key to male imagines of the subgenus is given.